Phytochemical characterization and anticancer potential of Psidium cattleianum Sabine aerial parts’ n-hexane extract and its subfractions - Eman M. El-Deeb; Fatma A. Moharram; Hussein S. Taha; Mohamed R. Elgindi; Kuei-Hung Lai; Hassan Y. Ebrahim; Heba E. Elsayed (PLoS ONE, 2025)
Psidium cattleianum Sabine (Family Myrtaceae) is a Brazilian native shrub, valued for its diverse health and therapeutic attributes. The current study investigated the phytochemical profile along with the anticancer activities of the n- hexane extract (HE) of P. cattleianum aerial parts and its subfractions. GC-MS and HPTLC-MS were used for phytochemical analysis. The human breast adenocarcinoma cells (MCF-7) and the human colon cancer cells (HCT-116) were used to investigate the anticancer effect in the viability, migration, and clonogenic assays. The GC-MS analysis of HE identified thirty-two components categorized mainly into terpenes, hydrocarbons, and sterols. β -caryophyllene oxide (12.07%) and humulene (7.42%) were the most abundant oxygenated and non-oxygenated metabolites, respectively. Concerning HE’s subfractions, fraction I is prolific with caryophyllene oxide (19.48%) and humulene (9.96%), while fraction II was rich in caryophyllene oxide (6.89%). HPTLC-MS analysis of fractions III-V identified the presence of nonadecatetraene, heptacosanol, and dihydroxy-oxo-ursenoic acid in fraction III; caryophyllene and littordial C in fraction IV, while guavanoic acid, p -coumaroyl caffeoylquinic acid, cholestane heptol, tocopherol, heptacosanedione, and trans -calamenene in fraction V. Concerning the anticancer results, the HE showed potent cytotoxicity with IC 50 29.18 ± 0.43 μg/mL (MCF-7) and 56.55 ± 6.8 μg/mL (HCT-116). In addition, at maximum tested doses approximating ½ IC 50 (15 and 28 μg/mL) in cytotoxicity assay, it displayed significant percent wound closure of 22.78 ± 2.13% and 12.76 ± 1.88%, respectively. While at doses corresponding to ¼ IC 50 (7.5 and 14 μg/mL), the HE displayed a colony formation efficiency of 2% and 0% on MCF-7 and HCT-116, respectively. Subfractions I and II, rich in caryophyllane sesquiterpenes, such as caryophyllene oxide, showed the best activity in all assays. Molecular docking of β -caryophyllene oxide, as the most identified bioactive metabolite, revealed an energetically favorable binding pose driven through hydrophobic interactions at the estrogen receptor ligand binding domain. The study endorses P. cattleianum HE and its selected fractions in the control of breast and colon cancers; however, further investigation into an appropriate in vivo model is required.